Operationalizing the One Health Approach via Health Information Systems: A Systematic Review of Enablers, Barriers, and Technological Innovations - Made Padma Puspita; Pande Putu Januraga; Ni Nyoman Sri Budayanti; Cokorda Rai Adi Pramartha; Nyoman Agus Jagat Raya (KHD Production, 2026)
The escalating complexity of global health challenges, including emerging infectious diseases and antimicrobial resistance, necessitates integrated frameworks connecting human, animal, and environmental health. This systematic literature review evaluated the current implementation of One Health principles within Health Information Systems (HIS) and identified associated integration opportunities and challenges. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we systematically searched Google Scholar, PubMed, ProQuest, ScienceDirect, and IEEE Xplore for literature published between 2015 and 2025. From an initial pool of 18,092 records, seven studies met the strict inclusion criteria for final qualitative synthesis, highlighting a significant gap in empirical cross-sectoral HIS research. Findings demonstrate that One Health-oriented HIS significantly enhances disease surveillance, facilitates intersectoral collaboration, and supports evidence-based decision-making. Technological innovations, notably mobile health (mHealth) and geographic information systems (GIS), drive these improvements by enabling real-time data collection and advanced spatial analysis across diverse ecological settings. Critical implementation barriers persist. Interoperability limitations, inadequate digital infrastructure, severe resource constraints, fragmented governance, and persistent cross-sector data-sharing challenges severely impede seamless system integration. Maximizing the effectiveness of One Health-based HIS requires strengthening policy frameworks, promoting universal interoperability standards, and investing heavily in foundational digital infrastructure. This review provides critical evidence to guide the development of robust, integrated health information systems that can improve global preparedness, surveillance, and response to complex, multisectoral health threats.